Optimalisasi Nilai Tambah Produksi Jagung Menjadi Marning di Kota Banjarbaru, Kalimantan Selatan - Surti; Aulia Rahmah; Puji Hastuti; Diah Ismayanti (JOURNAL OF ECONOMIC AND SOCIAL EMPOWERMENT, 2025)
This community service program aims to increase the added value of corn production by developing a corn morning business in Banjarbaru City. This program is motivated by the high production of corn, which reaches 29 tons per year, but its economic value has not been optimized. Through a comprehensive training and mentoring approach,the program involves 15 corn farmers as participants, focusing on four main aspects: production techniques, packaging according to PIRT, marketing strategies, and business management. The program's implementation lasts four days in October 2024, by presenting a combination of resource persons from successful MSME practitioners and academics. The methods used include lectures, discussions, demonstrations, and hands-on practice. The program results show participants have acquired basic knowledge and skills in corn marning processing, digital marketing, simple bookkeeping, business planning, and inventory management. This program is expected to encourage the growth of home-scale corn marning processing businesses that can increase the income of corn farmers in Banjarbaru.